2009
DOI: 10.1007/s00018-009-8476-0
|View full text |Cite
|
Sign up to set email alerts
|

Human stem cells as a model for cardiac differentiation and disease

Abstract: Studies on identification, derivation and characterization of human stem cells in the last decade have led to high expectations in the field of regenerative medicine. Although it is clear that for successful stem cell-based therapy several obstacles have to be overcome, other opportunities lay ahead for the use of human stem cells. A more immediate application would be the development of human models for cell-type specific differentiation and disease in vitro. Cardiomyocytes can be generated from stem cells, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 96 publications
0
21
0
Order By: Relevance
“…Among the regulatory factors identified in several groups of genes showing similar behavior (early downregulation, early upregulation, regulation during differentiation, fibronectin receptor complex), TGF-ß, TNF and BMP6 were identified. Temporal changes in the transcriptional profile of differentiating human ESC-derived CMs were investigated by Beqqali et al They showed that during differentiation of human ESCs, patterns of gene expression with early upregulation of embryonic genes followed by induction of mesoderm-specific and cardiac-specific genes occurred (25).…”
Section: Discussionmentioning
confidence: 99%
“…Among the regulatory factors identified in several groups of genes showing similar behavior (early downregulation, early upregulation, regulation during differentiation, fibronectin receptor complex), TGF-ß, TNF and BMP6 were identified. Temporal changes in the transcriptional profile of differentiating human ESC-derived CMs were investigated by Beqqali et al They showed that during differentiation of human ESCs, patterns of gene expression with early upregulation of embryonic genes followed by induction of mesoderm-specific and cardiac-specific genes occurred (25).…”
Section: Discussionmentioning
confidence: 99%
“…In stem cell research, a growing number of studies have been published the last decade focusing on cardiac regeneration [117,165] and on the pacemaker mechanism [166−172] . As hESCCMs usually start to beat spontaneously between the 9th and 12th day after differentiation begins, we focused our work on young cells (d11 to 21), which parallels the early beating cells of the cardiac tube [173] .…”
Section: The Calcium-activated Potassium Channel Familymentioning
confidence: 99%
“…ECM components considerably influence the growth characteristics of cardiomyocytes, development of physiological activities such as spontaneous contractile activity and phenotype morphological differentiation, suggesting synergestic effect of ECM components (Bick et al, 1998;. Elementary cardiac differentiation mechanisms have been elucidated using animal models along with in vitro models of cardiac development such as mouse embryonal carcinoma cells, mouse embryonic stem cells and recently, human embryonic stem cells (Kraehenbuehl et al, 2008;Beqqali et al, 2009). The growth rate and adhesion of murine mesenchymal stem cells in cardiogel were found to increase when co-cultured together .…”
Section: Cardiogel Supports Adhesion Proliferation and Differentiatimentioning
confidence: 99%